Preemption in Islamic and civil law a comparative study - Hamad, Dr. AdheedEzzat; Salih, Dr. Sawsan Safi; Mohammed, Bashar Kaiss (International Journal of Psychosocial Rehabilitation, 2020)
If the principle is that pre-emption leads to the forcible possession of property on the buyer, it restricts the latter from disposing of the real estate. However, jurisprudence agreed a long time ago that pre-emption is one of the most important Islamic organizations and therefore must be taken into account. It is not separated from its legal traditions and norms, and that interest is limited to reducing the number of partners in the property and the damage that lays in the complexity of disposition procedures as well as the exorbitant expenses and thus ending the common denominators through pre-Afad achieve this.